Inhibition of HIV-1 release by ADAM metalloproteinase inhibitors - Ireland, Joanna; Segura, Jason; Shi, Genbin; Buchwald, Julianna; Roth, Gwynne; Shen, Thomas Juncheng; Wang, Ruipeng; Ji, Xinhua; Fischer, Elizabeth R.; Moir, Susan; Chun, Tae-Wook; Sun, Peter D. (Frontiers in Microbiology, 2024)
HIV-1 gp120 glycan binding to C-type lectin adhesion receptor L-selectin/CD62L on CD4 T cells facilitates viral attachment and entry. Paradoxically, the adhesion receptor impedes HIV-1 budding from infected T cells and the viral release requires the shedding of CD62L. To systematically investigate CD62L-shedding mediated viral release and its potential inhibition, we screened compounds specific for serine-, cysteine-, aspartyl-, and Zn-dependent proteases for CD62L shedding inhibition and found that a subclass of Zn-metalloproteinase inhibitors, including BB-94, TAPI, prinomastat, GM6001, and GI25423X, suppressed CD62L shedding.Their inhibition of HIV-1 infections correlated with enzymatic suppression of both ADAM10 and 17 activities and expressions of these ADAMs were transiently induced during the viral infection. These metalloproteinase inhibitors are distinct from the current antiretroviral drug compounds. Using immunogold labeling of CD62L, we observed association between budding HIV-1 virions and CD62L by transmission electron microscope, and the extent of CD62Ltethering of budding virions increased when the receptor shedding is inhibited. Finally, these CD62L shedding inhibitors suppressed the release of HIV-1 virions by CD4 T cells of infected individuals and their virion release inhibitions correlated with their CD62L shedding inhibitions.Our finding reveals a new therapeutic approach targeted at HIV-1 viral release.